Formulation and evaluation of sustained release bioadhesive tablets of ofloxacin using 32 factorial design - Gangurde, Hemant H; Chordiya, Mayur A; Tamizharasi, S; Senthilkumaran, K; Sivakumar, T (International Journal of Pharmaceutical Investigation)
Background: Oral sustained release gastroretentive dosage forms offer many advantages for drugs having absorption from upper gastrointestinal tract and improve the bioavailability of medications that are characterized by narrow absorption window. The aim of current study was to design sustained release bioadhesive gastroretentive dosage form of ofloxacin. Materials and Methods: A 32 full factorial design was employed to systematically study the drug release profile and bioadhesive strength. Carbopol 934P and HPMC K100M were selected as the independent variables. Compatibility between drug and polymer was tested by fourier transform infrared (FTIR) and X-ray diffraction (XRD) techniques. Tablets were prepared by direct compression and were evaluated for tablet characteristics, swelling study, adhesion strength, percent drug released, radiographic imaging study and stability study. The optimized formulation was then compared with marketed formulation (Oflin OD;). Results: Tablets prepared showed good tablet characteristics, optimum swelling property, and good adhesion strength with high detachment force. Most of the formulations including the optimized formulation followed Higuchi kinetics and the drug release mechanism was found to be anomalous. Radiographic image proved that tablet remains intact in its structural integrity and shape in stomach up to 24 h. The short-term accelerated stability testing was carried out for the optimized formulation, and results revealed that drug content, in-vitro dissolution and all other parameters were within acceptable limits. Conclusion: Thus, the prepared bioadhesive gastroretentive ofloxacin tablet may prove to be a potential candidate which increases the bioavailability of ofloxacin for any intragastric condition.
Keywords: Bioadhesion; gastroretentive dosage form; ofloxacin; radiographic imaging study